Lower extremity reamputation in people with diabetes: a systematic review and meta-analysis - David G Armstrong; Brian J Petersen; Gary M Rothenberg; Rongqi Liu (BMJ Open Diabetes Research & Care)
In this study, we determined the reamputation-free survival to both limbs and to the contralateral limb only following an index amputation of any-level and assessed whether reamputation rates have changed over time. We completed a systematic search using PubMed and screened a total of 205 articles for data on reamputation rates. We reported qualitative characteristics of 56 studies that included data on reamputation rates and completed a meta-analysis on 22 of the studies which enrolled exclusively participants with diabetes. The random-effects meta-analysis fit a parametric survival distribution to the data for reamputations to both limbs and to the contralateral limb only. We assessed whether there was a temporal trend in the reamputation rate using the Mann-Kendall test. Incidence rates were high for reamputation to both limbs and to the contralateral limb only. At 1 year, the reamputation rate for all contralateral and ipsilateral reamputations was found to be 19% (IQR=5.1%–31.6%), and at 5 years, it was found to be 37.1% (IQR=27.0%–47.2%). The contralateral reamputation rate at 5 years was found to be 20.5% (IQR=13.3%–27.2%). We found no evidence of a trend in the reamputation rates over more than two decades of literature analyzed. The incidence of lower extremity reamputation is high among patients with diabetes who have undergone initial amputations secondary to diabetes, and rates of reamputation have not changed over at least two decades.